Relationship between maternal folic acid supplementation during pregnancy and risk of childhood asthma: Systematic review and dose-response meta-analysis - Yang, Fushuang; Zhu, Jinpu; Wang, Zhongtian; Wang, Lei; Tan, Tianhui; Sun, Liping (Frontiers in Pediatrics, 2022)
Growing evidence suggests that maternal folic acid supplementation during pregnancy may be associated with the risk of childhood asthma, but these findings remain controversial. Therefore, the purpose of this systematic review and meta-analysis was to assess the association between maternal folic acid supplementation during pregnancy and the risk of childhood asthma, and to determine the safe dose of folic acid supplementation during pregnancy based on a dose-response analysis to lower the risk of childhood asthma. The PubMed, Embase, Cochrane Library, and Web of Science databases were searched for relevant studies published before April 2022. The Newcastle-Ottawa Scale (NOS) was used to evaluate the quality of eligible studies, and a fixed-effect model was employed to calculate the odds ratio (OR) of asthma with 95% confidence intervals (CI). In addition, the generalized least-squares trend (GLST) was used to explore a nonlinear dose-response relationship. Stata 15.0 was used for the statistical analysis mentioned above. This systematic review included 18 studies (13 cohort studies, five case-control studies) with a total of 252,770 participants, 50,248 of whom were children with asthma. The meta-analysis showed that maternal folic acid supplementation during pregnancy was significantly associated with the risk of childhood asthma (OR = 1.07; 95% CI = 1.04-1.11). The subgroup analysis revealed a significant correlation between the risk of childhood asthma and the folic acid supplementation in the first Trimester (OR = 1.09; 95% CI = 1.05-1.12), the third Trimester (OR = 1.15; 95% CI = 1.04-1.26) and the whole pregnancy (OR = 1.13; 95% CI = 1.10-1.16). At the same time, the dose-response analysis showed a nonlinear relationship between maternal folic acid intake during pregnancy and the risk of childhood asthma. The risk of asthma in children significantly increased when maternal folic acid intake reached 581 μg/day. This meta-analysis showed that maternal folic acid supplementation during pregnancy increased the risk of asthma in children. Based on the results of the dose-response analysis, less than 580 μg folic acid per day is advised in order to effectively prevent birth defects without increasing the risk of childhood asthma.